Soil quality and soybean productivity in crop-livestock integrated system in no-tillage - Laroca, Jackeline Vieira dos Santos; Souza, Juliana Mendes Andrade de; Pires, Gabriela Castro; Pires, Gleidson José Coutinho; Pacheco, Leandro Pereira; Silva, Francine Damian da; Wruck, Flávio Jesus; Carneiro, Marco Aurélio Carbone; Silva,Laércio Santos; Souza, Edicarlos Damacena de (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the quality of the soil and its relation with soybean (Glycine max) yield in an integrated crop-livestock system (ICLS), with intercropping between grasses and legumes in the pasture phase. The experiment was carried out in the state of Mato Grosso, Brazil, on a dystrophic Oxisol, in which grasses (Megathyrsus maximus 'BRS Tamani' and Urochloa brizantha 'BRS Piatã'), intercropped with cowpea (Vigna unguiculata 'BRS Tumucumaque') and pigeon pea (Cajanus cajan 'BRS Mandarim'), were cultivated after soybean harvest. A randomized complete block design was used, with three replicates, in a split-plot arrangement, in which grasses were considered as plots, and legumes as subplots. Legume intercrops provided increases of C and total N stocks. The intercrops caused the increase of C and N of the microbial biomass, whereas the single cultures contributed to stress in the soil microbiota. The activity of the urease enzyme was sensitive to management changes in the short term, but acid phosphatase and β-glucosidase were poorly sensitive indicators. Soil quality is high with intercropping between grasses and legumes, with positive effects on soybean grain yield.